ANALYSIS OF THE INFLUENCE OF SALARY, LEADERSHIP STYLE, AND WORK ENVIRONMENT ON JOB SATISFACTION (CASE STUDY AT CHEVANI HOSPITAL, TEBING TINGGI CITY) - Cahyadi, Lukieto (International Conference on Health Science, Green Economics, Educational Review and Technology, 2020)
This study aims to determine the Analysis of the Effect of Wages, Leadership Style, and Work Environment on Job Satisfaction (Case Study at Chevani Hospital, Tebing Tinggi City). The research method used was a quantitative method using SPSS version 25.00 which was collected from the results of distributing questionnaires to hospital nurses. Chevani as many as 40 respondents. The analytical method used in this study is to use an instrument test, namely the validity and reliability test. The classical assumption test is the normality test, multicolonearity test, heteroscedasticity test, multiple linear regression analysis, analysis of the coefficient of determination (R2), hypothesis testing, namely the T test. (Y), the leadership style variable (X2) has no effect on the job satisfaction variable (Y),